2023
DOI: 10.1037/tra0001220
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and flourishing in the face of racial trauma.

Abstract: Objective: Examining well-being in the face of racial trauma is timely, clinically significant, and severely understudied, especially in Black populations. To address this gap, we investigated the relationship between flourishing and posttraumatic growth among Black undergraduates who reported a history of racial trauma. Method: Participants were 96 Black college students recruited from a predominantly White Midwestern university, all of whom reported experience of racial trauma. Participants completed the Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Additionally, resilience, fostered by collective experiences of overcoming adversity, may equip Black youth with the coping skills to resist peer pressure more effectively. This phenomenon underscores the importance of considering the protective factors that contribute to the health behaviors of minority youth, highlighting the need for nuanced approaches in public health strategies that go beyond the conventional understanding of risk factors [87,[93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, resilience, fostered by collective experiences of overcoming adversity, may equip Black youth with the coping skills to resist peer pressure more effectively. This phenomenon underscores the importance of considering the protective factors that contribute to the health behaviors of minority youth, highlighting the need for nuanced approaches in public health strategies that go beyond the conventional understanding of risk factors [87,[93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…Internal consistency scores supported the creation of a single composite score for each outcome. Both scales have been validated in African American populations (Grier-Reed et al, 2023; Keum et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Although not specific to sexual trauma, psychological flourishing as a measure of well-being may also be particularly important for Black young adults. For example, in a study of Black college students who self-reported having experienced racial trauma, posttraumatic growth—measured through the Posttraumatic Growth Inventory—significantly predicted self-perceptions of flourishing (Grier-Reed et al, 2023). It is possible that psychological flourishing could be an indicator of posttraumatic growth for Black survivors of sexual trauma, as well.…”
Section: Sexual Trauma Among Black Womenmentioning
confidence: 99%